2006
DOI: 10.1002/bem.20220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous and intermittent exposure to RF fields with a wide range of SARs on cell growth, survival, and cell cycle distribution

Abstract: To examine the biological effects of radio frequency (RF) electromagnetic fields in vitro, we have examined the fundamental cellular responses, such as cell growth, survival, and cell cycle distribution, following exposure to a wide range of specific absorption rates (SAR). Furthermore, we compared the effects of continuous and intermittent exposure at high SARs. An RF electromagnetic field exposure unit operating at a frequency of 2.45 GHz was used to expose cells to SARs from 0.05 to 1500 W/kg. When cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 13 publications
2
11
1
1
Order By: Relevance
“…Some studies have failed to find significant modifications in cell growth, cell survival and/ or cell cycle distribution on various in vitro systems [Higashikubo et al, 2001;Merola et al, 2006;Sekijima et al, 2010]. In contrast, other studies have reported altered cell proliferation after exposure to RF at doses above those applied in the present study [Cleary et al, 1996;Velizarov et al, 1999;Takashima et al, 2006]. Our results show that while the hepatocarcinoma HepG2 cell line does not seem to be sensitive to the RF treatment, the neuroblastoma NB69 cell line responded with a significant decrease in total cell number (13.5% below controls), together with increased rates of cells in phases G0/G1 (6% over controls) and G2/M (9% over controls) of the cell cycle.…”
Section: Discussioncontrasting
confidence: 61%
“…Some studies have failed to find significant modifications in cell growth, cell survival and/ or cell cycle distribution on various in vitro systems [Higashikubo et al, 2001;Merola et al, 2006;Sekijima et al, 2010]. In contrast, other studies have reported altered cell proliferation after exposure to RF at doses above those applied in the present study [Cleary et al, 1996;Velizarov et al, 1999;Takashima et al, 2006]. Our results show that while the hepatocarcinoma HepG2 cell line does not seem to be sensitive to the RF treatment, the neuroblastoma NB69 cell line responded with a significant decrease in total cell number (13.5% below controls), together with increased rates of cells in phases G0/G1 (6% over controls) and G2/M (9% over controls) of the cell cycle.…”
Section: Discussioncontrasting
confidence: 61%
“…The result is consistent with previous evidence, as the majority of studies have shown no effects on proliferation (Krause et al 1991, Stagg et al 1997, Vijayalaxmi et al 1997, Nikolova et al 2005, Lixia et al 2006, Merola et al 2006, Sanchez et al 2006, Scarfi et al 2006, Takashima et al 2006, Chauhan et al 2007). …”
Section: Discussionsupporting
confidence: 91%
“…Three studies have reported an increase in cellular proliferation (Cleary et al 1990a, 1990b, Velizarov et al 1999 and three studies have resulted in decreased proliferation (Cleary et al 1996, Kwee & Raskmark 1998, Capri et al 2004b. Several studies did not show any differences in proliferation between control and RF exposed cultures (Krause et al 1991, Stagg et al 1997, Vijayalaxmi et al 1997, Nikolova et al 2005, Lixia et al 2006, Merola et al 2006, Sanchez et al 2006, Scarfi et al 2006, Takashima et al 2006, Chauhan et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al (2002) reported that at SARs >20 W/kg, cell survival rates were reduced. In the recent report, Takashima et al (2006) compared the effects of continuous and intermittent exposure (2,450 MHz) at high SARs on cell growth, survival, and cell cycle distribution. When cells were exposed to a continuous RF fi eld at SARs from 0.05 to 100 W/kg for 2 h, cellular growth rate, survival, and cell cycle distribution were not affected.…”
Section: Cell Proliferationmentioning
confidence: 99%